Association of C677T polymorphism in the methylenetetrahydrofolate reductase gene (MTHFR gene) with ischemic stroke: a meta-analysis. (2nd June 2015) - Kumar, Amit; Kumar, Pradeep; Prasad, Manya; Sagar, Ram; Yadav, Arun Kumar; Pandit, Awadh Kishor; Jali, Vidishaa Prasad; Pathak, Abhishek
Abstract : Objective: Studies on association between methylenetetrahydrofolate r eductase gene (MTHFR) C677T gene polymorphism and ischemic stroke have shown conflicting results. We have conducted a meta-analysis to determine the precise association of the C677T polymorphism of MTHFR gene with risk of ischemic stroke. Materials and methods: We searched electronic databases Medline, EMBASE, and Google Scholar (last search dated till August 2014). Pooled odds ratios (ORs) with 95% confidence intervals (CIs) from random or fixed-effects models were calculated. The methodological quality of included studies was determined by the quality assessment scale. Results: Thirty eight case–control studies fulfilled our inclusion criteria comprising 6310 patients and 8297 controls. The significant associations between MTHFR C677T genetic polymorphism and risk of ischemic stroke were observed in dominant (OR, 1·09; 95% CI, 1·06–1·12, P -value < 0·001) and recessive (OR, 1·31; 95% CI, 1·19–1·44, P -value < 0·001) inheritance models. In an Asian population, significant association between the MTHFR polymorphism and ischemic stroke was observed (dominant model: OR 1·36, 95% CI 1·23–1·49 and under recessive model OR, 1·29; 95% CI, 1·15–1·45). In the Caucasian population borderline, non-significant association was observed under dominant model of inheritance (OR, 1·05; 95% CI, 0·99–1·10) but significant association was observed under the recessive model of inheritance (OR, 1·33; 95% CI, 1·13–1·58). Conclusion: The present study results suggest that MTHFR C677T genetic polymorphism is a probable risk of ischemic stroke.